2010
DOI: 10.1097/ijg.0b013e3181d13020
|View full text |Cite
|
Sign up to set email alerts
|

Myocilin Levels in Primary Open-angle Glaucoma and Pseudoexfoliation Glaucoma Human Aqueous Humor

Abstract: Purpose-To determine the concentration of myocilin in primary open-angle and pseudoexfoliation glaucoma aqueous humor.Methods-Aqueous humor was collected during surgery from patients with primary open-angle glaucoma (POAG), pseudoexfoliation glaucoma (PEXG), and elective cataract removal (control). Volume-equivalent aqueous samples were separated on SDS-PAGE gradient gels. Quantification of myocilin levels was performed using Western blots probed with two independent N-terminal polyclonal anti-myocilin antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
(33 reference statements)
2
17
0
Order By: Relevance
“…Myocilin levels were tested in control AH and compared to the levels of POAG and pseudoexfoliation glaucoma AH to determine whether levels of myocilin are altered in these glaucoma subsets. These levels were signifi cantly elevated in human POAG AH when compared with control AH (105) . A more recent study demonstrated that myocilin expression is not altered in the blood of POAG patients, unlike myocilin expression in the corresponding TM cultures (108) .…”
Section: Myocilinmentioning
confidence: 91%
See 3 more Smart Citations
“…Myocilin levels were tested in control AH and compared to the levels of POAG and pseudoexfoliation glaucoma AH to determine whether levels of myocilin are altered in these glaucoma subsets. These levels were signifi cantly elevated in human POAG AH when compared with control AH (105) . A more recent study demonstrated that myocilin expression is not altered in the blood of POAG patients, unlike myocilin expression in the corresponding TM cultures (108) .…”
Section: Myocilinmentioning
confidence: 91%
“…The protein is found in both intracellular and extracellular spaces, and has been linked to elevations in intraocular pressure. TM issue from POAG, low-tension glaucoma, and pseudoexfoliation glaucoma had increased myocilin immunoreactivity when compared to normal tissue (105) . Steroid treatment of monolayer TM cells or cultured human anterior segments showed a time and pressure dependent increase in myocilin protein production and secretion.…”
Section: Myocilinmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25][26][27][28] A great deal of effort has gone into exploring how these different bioactive agents influence TM tissue properties and cell biology in the context of AH outflow in both in vitro and in vivo studies. 15,16,24,[29][30][31][32][33][34][35][36] These efforts are beginning to unravel the participation of several different intracellular signaling mechanisms, including Rho GTPase, Wnt, ECM/ mechanotransduction, integrins, nitric oxide, PKC, BMPs/ SMADs, MAP kinases, and others, in regulating contractile properties of TM cells, ECM turnover, adhesive interactions, biomechanical properties, permeability, and survival of outflow pathway tissues and cells.…”
Section: Introductionmentioning
confidence: 99%